Reliability of human cortical organoid generation. (January 2019) - Yoon, Se-Jin; Elahi, Lubayna; Pașca, Anca; Marton, Rebecca; Gordon, Aaron; Revah, Omer; Miura, Yuki; Walczak, Elisabeth; Holdgate, Gwendolyn; Fan, H.; Huguenard, John; Geschwind, Daniel; et al.
Abstract The differentiation of pluripotent stem cells in three-dimensional cultures can recapitulate key aspects of brain development, but protocols are prone to variable results. Here we differentiated multiple human pluripotent stem cell lines for over 100 d using our previously developed approach to generate brain-region-specific organoids called cortical spheroids and, using several assays, found that spheroid generation was highly reliable and consistent. We anticipate the use of this approach for large-scale differentiation experiments and disease modeling. A protocol adapted to xeno- and feeder-free conditions is shown to generate reliable and consistent cortical brain organoids across differentiations and source stem cell lines, making it suitable for disease modeling and other applications.